Comprehensive analysis of mutations in the hepatitis delta virus genome based on full-length sequencing in a nationwide cohort study and evolutionary pattern during disease progression. (May 2015) - Shirvani-Dastgerdi, E.; Amini-Bavil-Olyaee, S.; Alavian, S. Moayed; Trautwein, C.; Tacke, F.
Abstract: Delta hepatitis, caused by co-infection or super-infection of hepatitis D virus (HDV) in hepatitis B virus (HBV) -infected patients, is the most severe form of chronic hepatitis, often progressing to liver cirrhosis and liver failure. Although 15 million individuals are affected worldwide, molecular data on the HDV genome and its proteins, small and large delta antigen (S-/L-HDAg), are limited. We therefore conducted a nationwide study in HBV-HDV-infected patients from Iran and successfully amplified 38 HDV full genomes and 44 L-HDAg sequences from 34 individuals. Phylogenetic analyses of full-length HDV and L-HDAg isolates revealed that all strains clustered with genotype 1 and showed high genotypic distances to HDV genotypes 2 to 8, with a maximal distance to genotype 3. Longitudinal analyses in individual patients indicated a reverse evolutionary trend, especially in L-HDAg amino acid composition, over time. Besides multiple sequence variations in the hypervariable region of HDV, nucleotide substitutions preferentially occurred in the stabilizing P4 domain of the HDV ribozyme. A high rate of single amino acid changes was detected in structural parts of L-HDAg, whereas its post-translational modification sites were highly conserved. Interestingly, several non-synonymous mutations were positively selected that affected immunogenic epitopes of L-HDAg towards CD8 T-cell- and B-cell-driven immune responses. Hence, our comprehensive molecular analysis comprising a nationwide cohort revealed phylogenetic relationships and provided insight into viral evolution within individual hosts. Moreover, preferential areas of frequent mutations in the HDV ribozyme and antigen protein were determined in this study.